1. Wykonaj działania :
a) 6(x-4)- 2=
b) 2(x+1)- 3(x+1)=
c) -3(y-2) + 4(y+2) =
d) 5(x-y-1) - 4(x+2)=
e) 2(3a + b) - 2(a- b )=
f) ½(4x - 4) - 2x =
g) x(x-1) - 3(x² - x)=
h) 5a(a-3) - 3a(a-5)=
i) 3x(x+⅓ y ) - 2y (½x - ½)=

2.Uprość podane wyrażenie :
4 * (x-7) :2 + 9 * (x-1) : 3 =

z.3 Wyłącz wspólny czynnik przed nawias :
a) 5x + 10y =
b) 4m + 4 =
c) 3a- 3 =
d) 5xy - x =
e) -6a² - 2a =
f) 6a² - 12ab =
g) ½ xy - ½x =
h) ⅓ a²b + 1/9ab² =
i) 2xyz - 4x²y²z + xyz² =
j) stv² - stv + tv² =
* 1/9 = jedna dziewiąta
-----------
z. 4 Zapisz w postaci iloczynu :
a) ½ * 4(a+b) - ½h(a+b) =
b) z(x-y)-(y-x) =
PROSZE TO NA JUTRO . DAM NAJ :))

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T20:45:51+01:00
1. Wykonaj działania :
a) 6(x-4)- 2=6x-24-2=6x-26
b) 2(x+1)- 3(x+1)=2x+2-3x-3=-x-1
c) -3(y-2) + 4(y+2) =-3y+6+4y+8=y+14
d) 5(x-y-1) - 4(x+2)=5x-5y-5-4x-8=x-5y-13
e) 2(3a + b) - 2(a- b )=6a+2b-2a-2b=4a
f) ½(4x - 4) - 2x =2x-1-2x=-1
g) x(x-1) - 3(x² - x)=x²-x-3x²+3x=2x²+2x
h) 5a(a-3) - 3a(a-5)=5a²-15a-3a²-15a=2a²
i) 3x(x+⅓ y ) - 2y (½x - ½)=3x²+1y-1x-y=3x²-1x

2.Uprość podane wyrażenie :
4 * (x-7) :2 + 9 * (x-1) : 3 =4x-28:2+9x-9:3=13x-14-3=13x-17

z.3 Wyłącz wspólny czynnik przed nawias :
a) 5x + 10y =5(x+2y)
b) 4m + 4 =4(m+1)
c) 3a- 3 =3(a+1)
d) 5xy - x =x(5y)


2010-03-10T21:01:10+01:00
Ad1) 6(x-4)-2= 6x-24-2=6x-26
2(x+1)-3(x+1)= 2x+2-3x-3= -x-1
-3(y-2) + 4(y+2) =-3y+6+4y+8=y+14
5(x-y-1) - 4(x+2)= 5x-5y-5-4x-8= x-5y-13
2(3a + b) - 2(a- b )=6a+2b-2a+2b= 4a+4b
½(4x - 4) - 2x =2x-2-2x= -2
x(x-1) - 3(x² - x)=x²-x-3x²+3x = -2x²+2x
5a(a-3) - 3a(a-5)= 5a²-15a-3a²+15a= 2a²
3x(x+⅓ y ) - 2y (½x - ½)=3x²+y-xy+y = 3x²+2y-xy

2.Uprość podane wyrażenie :
4 * (x-7) :2 + 9 * (x-1) : 3 = (4x-28):2+ (9x-9):3= 2x-14+3x-3= 5x-17

z.3 Wyłącz wspólny czynnik przed nawias :
a) 5x + 10y = 5(x+2y)
b) 4m + 4 = 4(m+1)
c) 3a- 3 = 3(a-1)
d) 5xy - x = x(5y-1)
e) -6a² - 2a = -2a(3a+1)
f) 6a² - 12ab = 6a(a-2b)
g) ½ xy - ½x = ½x(y-1)
h) ⅓ a²b + 1/9ab² = ⅓ ab(a+⅓ b)
i) 2xyz - 4x²y²z + xyz² = xyz(2-4xy+z)
j) stv² - stv + tv² =tv(sv-s+v)